Wake characterization of paired cross-flow turbines. (August 2022) - Posa, Antonio
Abstract: The wake of paired cross-flow turbines is reproduced by means of Large-Eddy Simulation, using a computational grid consisting of about two billion points. The role of mutual interaction and secondary flows on the process of wake recovery is revealed across three different systems. The comparison across cases shows that the blockage effects and cross-flows are best exploited, with the purpose of a faster recovery in the region downstream of the turbines, when they are counter-rotating, sharing their leeward sides. This is also the paired system showing the lowest values of turbulent kinetic energy in the area just behind the upstream turbines, where other devices are supposed to be placed in typical staggered arrays or triangular units. This result is in qualitative agreement with an earlier study [1], where spanwise homogeneity of the flow was assumed, but it takes into account the important contribution by spanwise flows, promoting momentum influx from the free-stream at the spanwise boundaries of the wake and accelerating the process of wake recovery.